Filled carbon nanotubes in biomedical imaging and drug delivery. (April 2015) - Martincic, Markus; Tobias, Gerard
<x xml:space="preserve">Abstract</x> Introduction: Carbon nanotubes have been advocated as promising candidates in the biomedical field in the areas of diagnosis and therapy. In terms of drug delivery, the use of carbon nanotubes can overcome some limitations of 'free' drugs by improving the formulation of poorly water-soluble drugs, allowing targeted delivery and even enabling the co-delivery of two or more drugs for combination therapy. Two different approaches are currently being explored for the delivery of diagnostic and therapeutic agents by carbon nanotubes, namely attachment of the payload to the external sidewalls or encapsulation into the inner cavities. Although less explored, the latter confers additional stability to the chosen diagnostic or therapeutic agents, and leaves the backbone structure of the nanotubes available for its functionalization with dispersing and targeting moieties. Several drug delivery systems and diagnostic agents have been developed in the last years employing the inner tubular cavities of carbon nanotubes. Areas covered: The research discussed in this review focuses on the use of carbon nanotubes that contain in their interior drug molecules and diagnosis-related compounds. The approaches employed for the development of such nanoscale vehicles along with targeting and releasing strategies are discussed. Expert opinion: The encapsulation of both biomedical contrast agents and drugs inside carbon nanotubes is further expanding the possibilities to allow an early diagnosis and treatment of diseases.